Supervisory Function And Earnings Quality: Gender Analysis - Deden Tarmidi; Nurlis; Sormin, Feber; Prihanto, Hendi; Saputri, Zinka (Jurnal Akuntansi, 2024)
Gender analysis of independent commissioners and audit committees in carrying out supervisory functions and their impact on the entity’s earnings quality is the purpose of this study. With the unit of analysis of manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2021, using multiple linear regression analysis methods with STATA software in analysing 745-panel data, this study found a positive effect of multi-gender independent commissioners on earnings quality but has a negative impact on mono-gender where female independent commissioners are more significant than male. While gender diversity in the audit committee does not affect earnings quality, even so, the supervisory function carried out by the male audit committee is more significantly positive than that of the female. Based on these results, owners can appoint multi-gender independent commissioners and mono-gender audit committees for proper supervisory functions, especially in preparing financial statements to improve earnings quality.